Clinical Outcome of Percutaneous Iliosacral Screw Fixation in Unstable Pelvic Ring Injury - Dawadi, Tej Prakash; Regmi, Anand Prasad; Sitaula, Jyoti; Sharma, Bishnu Dev; Shrestha, Sujit Raj; Rijal, Sanjeev; Acharya, Devendra; KC, Saugaat (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Surgical fixation of unstable pelvic injuries improves fracture reduction, early weight bearing and mobilization, lower mortalities, shorter hospital stays, and superior functional outcomes compared with non-operative treatment. The minimal invasive Iliosacral screws have improved outcomes, reduced complication rates as well as operative time. We aim to find out clinical outcome of percutaneously placed Iliosacral screw in unstable pelvic ring injury in our hospital and also compare our data with the availabale relevent literatureMETHODS A total of 33 cases underwent Iliosacral screw fixation for unstable pelvic ring injury with a complete follow-up of one year. VAS and Majeed pelvic scores were calculated to assess the functional outcome of the surgery.RESULTS The median age of the patients was 35 (20-87). The median duration of surgery for the iliosacral screw was 56 (41- 81) minutes. After 1 year of follow-up, the median VAS score was 1 (1-2). The mean Majeed pelvic score was 86.12 ± 5.57. Excellent results were seen in 23 (69.69%) cases and good results were seen in 9 (27.27%) cases.CONCLUSIONPercutaneous Iliosacral screw fixation has a favourable outcome in unstable pelvic ring injury.